Antidepressant Medication Use and Its Association With Cardiovascular Disease and All-Cause Mortality in the Reasons for Geographic and Racial Differences in Stroke (REGARDS) Study. (April 2016) - Hansen, Richard A.; Khodneva, Yulia; Glasser, Stephen P.; Qian, Jingjing; Redmond, Nicole; Safford, Monika M.
Background: Mixed evidence suggests that second-generation antidepressants may increase the risk of cardiovascular and cerebrovascular events.Objective: To assess whether antidepressant use is associated with acute coronary heart disease (CHD), stroke, cardiovascular disease (CVD) death, and all-cause mortality.Methods: Secondary analyses of the Reasons for Geographic and Racial Differences in Stroke (REGARDS) longitudinal cohort study were conducted. Use of selective serotonin reuptake inhibitors, serotonin and norepinephrine reuptake inhibitors, bupropion, nefazodone, and trazodone was measured during the baseline (2003-2007) in-home visit. Outcomes of CHD, stroke, CVD death, and all-cause mortality were assessed every 6 months and adjudicated by medical record review. Cox proportional hazards time-to-event analysis followed patients until their first event on or before December 31, 2011, iteratively adjusting for covariates.Results: Among 29 616 participants, 3458 (11.7%) used an antidepressant of interest. Intermediate models adjusting for everything but physical and mental health found an increased risk of acute CHD (hazard ratio [HR] = 1.21; 95% CI = 1.04-1.41), stroke (HR = 1.28; 95% CI = 1.02-1.60), CVD death (HR = 1.29; 95% CI = 1.09-1.53), and all-cause mortality (HR = 1.27; 95% CI = 1.15-1.41) for antidepressant users. Risk estimates trended in this direction for all outcomes in the fully adjusted model but only remained statistically associated with increased risk of all-cause mortality (HR = 1.12; 95% CI = 1.01-1.24). This risk was attenuated in sensitivity analyses censoring follow-up time at 2 years (HR = 1.37; 95% CI = 1.11-1.68).Conclusions: In fully adjusted models, antidepressant use was associated with a small increase in all-cause mortality.